Association between the frequency of disposable diaper changing and urinary tract infection in children - Meirina Daulay; Rosmayanti Siregar; Oke Rina Ramayani; Supriatmo Supriatmo; Rafita Ramayati; Rusdidjas Rusdidjas (Indonesian Pediatric Society, 2013)
Background Urinary tract infection (UTI) is the most commoncause of fever in children. Less frequent disposable diaper changingis thought to be a cause ofUTI in children. While wearing a diapei;the perinea! area becomes damp with urine allowing bacteria tomigrate from the anus to the external urethral orifice.Objective To assess for an association between the frequencyof disposable diaper changing and urinary tract infections inchildren.Methods This cross-sectional study was conducted in thechildren's outpatient clinic of Haji Adam Malik Hospital fromApril to June 2010. Urine culture was performed in children withsuspected UTI who wore disposable diapers every day. Subjects'ages ranged from 2 months to 2 years 6 months, with samplesmatched and collected by consecutive sampling. Diagnosis ofUTIwas based on urine cultures with bacterial count 2:: 105/mL. Eightychildren were followed in this study and divided into two groups:positive (n=40) and negative (n=40) urine cultures. Chi squaretest was use d to analyze the association between the frequency ofdaily disposable diapers changing during a one week period andthe urine culture results.Results The frequency of daily disposable diapers changing in80 subjects was as follows: < 4 times (22.5%), 4-5 times (40%),and 2::6 times (37.5%) . The frequency of daily disposable diaperchanging in children with positive urine culture was as fo llows:< 4 times (1 8 out of 40), 4-5 times (22 out of 40), and 2::6 times(O out of 40); (P < 0.0001). The most common bacterial speciesfound in urine cultures was Escherichia coli.Conclusion Lower frequency of daily disposable diaper changingis significantly associated with higher UTI incidence in children.